2016
DOI: 10.1017/rdc.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Online 13C and 14C Gas Measurements by EA-IRMS–AMS at ETH Zürich

Abstract: Studies using carbon isotopes to understand the global carbon cycle are critical to identify and quantify sources, sinks, and processes and how humans may impact them. 13C and 14C are routinely measured individually; however, there is a need to develop instrumentation that can perform concurrent online analyses that can generate rich data sets conveniently and efficiently. To satisfy these requirements, we coupled an elemental analyzer to a stable isotope mass spectrometer and an accelerator mass spectrometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…The sample was then wrapped in tinfoil boats (Elementar), pressed, and 335 analysed using a coupled elemental analyser-isotope ratio mass spectrometer-accelerator mass spectrometer (EA-IRMS-AMS) system at ETH Zurich Wacker et al, 2010). The instrumental set-up, blank assessment, accuracy, and reproducibility for the data presented here have been previously reported in McIntyre et al (2016). 340…”
Section: Bulk Elemental and Isotopic Analysismentioning
confidence: 99%
“…The sample was then wrapped in tinfoil boats (Elementar), pressed, and 335 analysed using a coupled elemental analyser-isotope ratio mass spectrometer-accelerator mass spectrometer (EA-IRMS-AMS) system at ETH Zurich Wacker et al, 2010). The instrumental set-up, blank assessment, accuracy, and reproducibility for the data presented here have been previously reported in McIntyre et al (2016). 340…”
Section: Bulk Elemental and Isotopic Analysismentioning
confidence: 99%
“…Terrestrial carbon turnover time remains one of the largest uncertainties in climate model predictions (Carvalhais et al, 2014;He et al, 2016). At present, there is no consensus on the net effect that climate and land use change will have on SOM stocks (Crowther et al, 2016;Gosheva et al, 2017;Melillo et al, 2002;Schimel et al, 2001;Trumbore and Czimczik, 2008). Deep soil carbon is of particular interest because of its large stocks (Jobbagy and Jackson, 2000;Balesdent et al, 2018;Rumpel and Kögel-Knabner, 2011) and perceived stability.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the so-called "bomb radiocarbon spike" will continue to diminish in the coming decades, time-series measurements are increasingly a matter of urgency in order to take full advantage of this intrinsic tracer (Graven, 2015). Several case studies have collected time-series 14 C soil datasets and demonstrated the value of this approach (Baisden and Parfitt, 2007;Prior et al, 2007;Fröberg et al, 2010;Mills et al, 2013;Schrumpf and Kaiser, 2015). However, these studies are rare, based on single specific sites, and have been rarely linked to abiotic and biotic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Fumigated samples were analyzed on a MICADAS system (MIni CArbon DAting System) at ETH Zürich. The accelerator mass spectrometer was run in gas mode and configured to run with the elemental analyzer and the gas interface system using a method modified to incorporate a stable isotope ratio mass spectrometer (Ruff et al ; Fahrni et al ; McIntyre et al ). Radiocarbon ages were calibrated using the Marine 13 curve with the Oxcal software v 4.3.…”
Section: Methodsmentioning
confidence: 99%